Proteomics disclose the effect of carbaon and nitrogen sources on GABA production by Levilactobacillus brevis CRL 2013 - Cataldo, Pablo Gabriel (2022)
Gamma-aminobutyric acid (GABA) is a non-protein amino acid, which functions as the main inhibitory neurotransmitter in humans showing potential for improving several mental health conditions such as stress and anxiety. The microbiota-gut-brain axis is a bidirectional communication pathway between the central nervous system and the gut microbiota, which is mediated by several direct and indirect stimuli. Microbial GABA synthesis within the gut can affect host mental health outcomes. In bacteria, GABA is produced and released by the glutamate decarboxylase (GAD) system, which consists of three key elements: the positive transcriptional regulator (GadR), the glutamate/GABA antiporter (GadC) and the glutamate decarboxylase enzymes (GadA and/or GadB). Understanding the molecular characteristics of GABA production by the microbiota can provide insights into new therapies for mental health. Therefore, the aim of this study was to assess the effect of different nitrogen; yeast extract (YE) and casitone (C); and carbon (hexose and pentose) sources on the fermentation profile and GABA production by the efficient GABA producer, Levilactobacillus (L.) brevis CRL 2013 strain and explore the associated proteomic changes. GABA accumulated up to 72 h in glucose and fructose- CDM (CDMGF) supplemented with YE and C; this was related to a reduction in glutamate concentration and an increase in the extracellular pH. Lactic acid, acetic acid, and ethanol (2.5 g/L) could be detected in the fermented medium. In CDM-Xylose (CDMX), the cell density was markedly higher than in CDMGF, presenting the highest values of lactic (5.6 g/L) and acetic (3 g/L) acids while ethanol was not detected. Moreover, GABA production decreased about 13 times and the amount of residual glutamate was significantly higher (9 times) with respect to the CDMGF. The initial addition of ethanol to the CDMX increased both GABA production and the levels of organic acids. The proteomic data revealed that GadA was upregulated in CDMGF in the presence of YE and C (294 and 50 times, respectively). Under these conditions, GadB expression remained unchanged, whereas CcpA and HPr kinase were upregulated after YE and C supplementation (3.7 and 2-fold respectively). Furthermore, YE and C supplementation in the CDMGF induced the differential expression of proteases and peptidases. These expression trends were confirmed by transcriptional assays (RT-qPCR) with recA as the housekeeping gene. Additionally, ethanol supplementation increased gadA expression in the CDMX. Our results expand knowledge about the regulation of the GAD system in lactic acid bacteria, where carbon and nitrogen sources as well as some fermentation by-products may play a key role and support the use of L. brevis CRL2013 as a microbial cell factory for the efficient production of GABA using alternative energy sources.